A Review of Infants With Localized Neuroblastoma That Evolve to Stage 4s Disease. Issue 6 (August 2020) - Caroleo, Anna M.; De Bernardi, Bruno; Avanzini, Stefano; Gigliotti, Anna R.; Muraca, Monica; Pota, Elvira; Provenzi, Massimo; Mazzocco, Katia; Sementa, Angela R.; Granata, Claudio; Sorrentino, Stefania
Abstract : The authors describe a newborn diagnosed with localized neuroblastoma that evolved to stage 4s at the age of 5 months. Peculiar features of the case included a bilateral adrenal primary, the skin as the only metastatic site, and the development of a muscular lesion late in the clinical course. The patient underwent left adrenalectomy and all other lesions regressed without further therapy. The case prompted a search for similar cases both in the Italian Neuroblastoma Registry and in the literature. All patients identified, although variously treated, survived with the exception of the 2 with MYCN gene amplification. We conclude that infants with neuroblastoma who undergo a transition from a localized to stage 4s disease could be less rare than expected. In the absence of unfavorable biology, a wait-and-see policy with strict follow-up could be adopted for these patients, avoiding potentially damaging systemic therapy.